THE INFLUENCE OF HIGHER EDUCATION IN IMPROVING WOMEN’S SOCIAL STATUS: AN EMPIRICAL EVIDENCE FROM LAHORE, PAKISTAN - Nawaz, Muhammad; Ramzan, Beenish; Muhammad, Nadeem; Bhatti, Ghulam Abbas; Nadeem, Arooj (International Journal of Research -GRANTHAALAYAH, 2017)
Education have great deal of importance in every aspect of life, thus, this study deals with its one foremost aspect by investigating the impact of higher education on women’s social status. The social status of working women was examined by women’s perception about their decision-making participation at the household level in Lahore. The social impact of higher education was evaluated based on positivist philosophy and implantation of survey approach. Primary data have been collected using self-administered questionnaire. A sample of 120 women respondents studying and teaching at National College of Business Administration & Economics was collected using the simple random technique. A Chi-square test of homogeneity was applied to see whether the difference in the proportion of opinion responses. The study found that highly educated women were more socially empowered than the less educated women and actively participate in familial related decision makings.